Flame-made Pt-loaded TiO2 thin films and their application as H2 gas sensors - Weerasak Chomkitichai (2018)
The hydrogen gas sensors were developed successfully using flame-made platinum-loaded titanium dioxide (Pt-loaded TiO2) nanoparticles as the sensing materials. Pt-loaded TiO2thin films were prepared by spin-coating technique onto Al2O3substrates interdigitated with Au electrodes. Structural and gas-sensing characteristics were examined by using scanning electron microscopy (SEM) and showed surface morphology of the deposited film. X-ray diffraction (XRD) patterns can be confirmed to be the anatase and rutile phases of TiO2. High-resolution transmission electron microscopy (HRTEM) showed that Pt nanoparticles deposited on larger TiO2nanoparticles. TiO2films loaded with Pt nanoparticles were used as conductometric sensors for the detection of H2. The gas sensing of H2was studied at the operating temperatures of 300, 350, and 400°C in dry air. It was found that 2.00 mol% Pt-loaded TiO2sensing films showed higher response towards H2gas than the unloaded film. In addition, the responses of Pt-loaded TiO2films at all operating temperatures were higher than that of unloaded TiO2film. The response increased and the response time decreased with increasing of H2concentrations. © 2013 Weerasak Chomkitichai et al.